The Green Economy for a Sustainable Future: Experience from the Visegrad Group Countries - Klimko, Roman (Comparative Economic Research. Central and Eastern Europe, 2025)
The objective of this paper is to identify the significance of the green economy for a sustainable future and compare the situation and developments in achieving the European Green Deal (EGD) in the Visegrad Group (V4) countries. To achieve this objective, the paper focuses on the challenges, risks and opportunities of implementing green economy policies. Comprehensive data analysis is conducted, and a European Green Deal Index (EGDI) for the V4 countries is developed. The Eurostat database is used to monitor 18 key indicators in the V4 countries from 2015 to the latest year available. The results show that Slovakia is the best-performing V4 country with the highest EGDI score, while Poland shows the most significant improvement, mainly in the category Enabling a green and just transition. Between 2015 and 2023, Slovakia and Czechia experienced negative trends in the percentage of the population unable to keep their home adequately warm for financial reasons. The paper highlights the social dimension of the EGD and the green economy as well as the importance of a just transition concept across the whole European Union since increased household spending on the green transition could affect public support.